2016
DOI: 10.5858/arpa.2016-0331-cp
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Testing and Clinical Decision Making in Gastroesophageal Adenocarcinoma: Guideline From the College of American Pathologists, American Society for Clinical Pathology, and American Society of Clinical Oncology

Abstract: - This guideline provides specific recommendations for assessment of HER2 in patients with advanced GEA while addressing pertinent technical issues and clinical implications of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 123 publications
1
121
0
1
Order By: Relevance
“…Some recommended such cases should be subjected to in situ hybridization (ISH) test, and if amplification was detected, the case should be considered positive [6, 18]. A recent consensus from the College of American Pathologists, American Society for Clinical Pathology, and American Society of Clinical Oncology indicated that following the Ruschoff/Hofmann method, IHC results should be scored based on the staining pattern which accounted for ≥ 10% of tumor cells, and whether to perform ISH was determined by the IHC score [9]. Based on the current study, it might be reasonable to deduce that HER2 focal positive(< 10%) cases may also be eligible for trastuzumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recommended such cases should be subjected to in situ hybridization (ISH) test, and if amplification was detected, the case should be considered positive [6, 18]. A recent consensus from the College of American Pathologists, American Society for Clinical Pathology, and American Society of Clinical Oncology indicated that following the Ruschoff/Hofmann method, IHC results should be scored based on the staining pattern which accounted for ≥ 10% of tumor cells, and whether to perform ISH was determined by the IHC score [9]. Based on the current study, it might be reasonable to deduce that HER2 focal positive(< 10%) cases may also be eligible for trastuzumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 status has been studied extensively in GC, and criteria for HER2 interpretation has been established and standardized during these years [69]. HER2 is associated with Lauren classification, and HER2 positive GCs are mainly intestinal type [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of HER3 expression was performed by an experienced gynecological pathologist and two additional observers that independently evaluated HER3 scores in accordance with the HER2 testing guidelines for gastroesophageal cancer from the College of American Pathologists, American Society for Clinical Pathology, and American Society of Clinical Oncology ( 19 ). High HER3 expression (HER3-high) was defined as a score of 2+ or 3+, and low HER3 expression (HER3-low) was defined as a score of 0 or 1+; discrepancies were resolved by discussion and consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Her2 testing methods and algorithm for EAC is similar to those in gastric adenocarcinoma, first by immunohistochemistry (IHC) followed by in situ hybridization (ISH) when immunohistochemistry result is 2+ (equivocal). Positive (3+) or negative (0 or 1+) immunohistochemistry results do not require further ISH testing [72]. Her2 IHC is graded as negative 0 (on membranous staining in any of the tumor cells), negative 1+ (faint/barely perceptible membranous staining), equivocal 2+ (weak to moderate, complete, basolateral and lateral membranous staining), and positive 3+ (strong, complete, basolateral and lateral membranous staining) and the cutoff of at least 10% of tumor resection specimen or a small cluster of at least 5 tumor cells in biopsy specimen is used [72].…”
Section: Ancillary Biomarkers For Be Dysplasia and Early Stage Eacmentioning
confidence: 99%
“…Positive (3+) or negative (0 or 1+) immunohistochemistry results do not require further ISH testing [72]. Her2 IHC is graded as negative 0 (on membranous staining in any of the tumor cells), negative 1+ (faint/barely perceptible membranous staining), equivocal 2+ (weak to moderate, complete, basolateral and lateral membranous staining), and positive 3+ (strong, complete, basolateral and lateral membranous staining) and the cutoff of at least 10% of tumor resection specimen or a small cluster of at least 5 tumor cells in biopsy specimen is used [72]. Cases with Her2 equivocal 2+ IHC result should be tested by ISH for Her2 amplification with positivity defined as Her2/CEP17 ratio ≥2.…”
Section: Ancillary Biomarkers For Be Dysplasia and Early Stage Eacmentioning
confidence: 99%